2011
DOI: 10.1007/s12663-011-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Extended Nasolabial Flaps in the Management of Oral Submucous Fibrosis

Abstract: Purpose We evaluated the use of extended nasolabial flaps in the management of oral submucous fibrosis. Methods We evaluated the use of extended nasolabial flaps in the management of 27 randomly selected patients with histologically confirmed oral submucous fibrosis. They all had interincisal opening of less than 20 mm and were treated by bilateral release of fibrous bands and extended grafting with a nasolabial flap. All patients had postoperative physiotherapy, and were followed up for one year.Results Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Interestingly use of free flaps for surgical management of OSMF has been reported only from the Chinese subcontinent with no reports available from other regions of the world. Five studies using a split technique of a radial forearm free flap from a single donor site and a single study using a similar split flap harvested from anterolateral thigh based on the lateral dorsal circumflex artery have been described [36][37][38][39][40] (Table 6). All the studies reported common complications of aberrant microvascular stenosis in the anastomoses and need for debulking at a later stage.…”
Section: Extraoral Flapsmentioning
confidence: 99%
“…Interestingly use of free flaps for surgical management of OSMF has been reported only from the Chinese subcontinent with no reports available from other regions of the world. Five studies using a split technique of a radial forearm free flap from a single donor site and a single study using a similar split flap harvested from anterolateral thigh based on the lateral dorsal circumflex artery have been described [36][37][38][39][40] (Table 6). All the studies reported common complications of aberrant microvascular stenosis in the anastomoses and need for debulking at a later stage.…”
Section: Extraoral Flapsmentioning
confidence: 99%
“…In the year 2011, Agarwal et al [ 10 ] performed a study to evaluate the use of extended nasolabial flaps in the management of oral submucous fibrosis in which they encountered intraoral hair growth in men. Likewise, in our case series intraoral hair growth was a common manifestation postoperatively in males which was gradually reduced over a period of one year.…”
Section: Discussionmentioning
confidence: 99%
“…10). This flap has become popular in the treatment of limitations in mouth opening of patients with oral submucosal fibrosis with vertical mucosal bands in the cheek concomitant with coronoidectomy [74], [75], [76], [77].…”
Section: Discussionmentioning
confidence: 99%